Position of Nepali Congress in the Electoral Politics of Nepal - Shrestha, Amrit Kumar (Researcher: A Research Journal of Culture and Society, 2020)
Nepali Congress (NC) is one of the oldest political party of Nepal. It played a vital role to abolish the century long autocratic Rana rule in 1951. It fought against the party-less Panchayat system and the regressive step of the king. It opposes active kingship and communism. It believes in a representative democracy. It has participated in every election of Nepal that was conducted democratically. It won more than two-thirds majority seats in the first general election held in 1959. In every election, it stayed in the first or second position. This article tries to analyze the status of NC in the elections of Nepal. Data of seven general elections were examined in this article. Data were extracted basically from the reports of the Election Commission.